2018
DOI: 10.1016/j.clae.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact lens surface properties on comfort, tear stability and ocular physiology

Abstract: As previously hypothesised, enhancing the physical surface properties of a soft contact lens improves subjectively rated wearer comfort, which, in turn, should result in reduced contact lens discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 40 publications
1
61
0
Order By: Relevance
“…There have been some articles that have talked specifically about materials for contact lenses, which provided important insights at the time [32,33]. Other sources have discussed general bioavailable materials [34,35] and the properties of CL brands [33], with a lot of modern research being concerned about drug delivery using CLs [27,36,37,38]. This review brings together research specifically about the latest development of CL materials, and touches on details from a materials science perspective.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some articles that have talked specifically about materials for contact lenses, which provided important insights at the time [32,33]. Other sources have discussed general bioavailable materials [34,35] and the properties of CL brands [33], with a lot of modern research being concerned about drug delivery using CLs [27,36,37,38]. This review brings together research specifically about the latest development of CL materials, and touches on details from a materials science perspective.…”
Section: Introductionmentioning
confidence: 99%
“…in the SiHy core to the design of sophisticated CL surfaces with high water holding properties. The SiHy studied are chosen to present these distinct approaches [7][8][9] : narafilcon A (NarA), senofilcon A (SenA), stenfilcon A (StenA) and delefilcon A (DelA). NarA and SenA are SiHy materials with 48% and 38% water content, respectively, and no surface coating; polyvinylpyrrolidone based internal wetting agent is utilized instead.…”
Section: Introductionmentioning
confidence: 99%
“…Thus although no previous studies are reported in this regard, it can be expected that wettability may influence SiHy lubricity. 8,10,11 Secondly, the studies are commonly performed with fresh hydrated samples just removed from the blister solution, which neglects the alterations occurring in the CL due to accumulation of desiccation stress in the course of daily wear. 8 Therefore, the aim of the current study is to probe simultaneously the changes that occur in the water content, the wettability and the coefficient of friction (CoF) of these four diverse silicone hydrogels in the course of blink-like desiccation (10 s)/rehydration (1 s) cycling and to analyze the relationship between these properties at a time scale matching the duration of extended daily wear of the CL (0 i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it is the higher coefficient of friction (CoF) in contact lens compared to an ocular surface without contact lens that may be a major contributor for the difference in LWE. 57,58 CoF is defined as the relationship of friction between two interfacing surfaces, with contact lens CoF determined by material, as well as deposits that develop during wear. 13 The importance of contact lens CoF is highlighted by studies that suggest that its increase may be associated with increased contact lens discomfort and corneal staining.…”
Section: 13mentioning
confidence: 99%
“…13 The importance of contact lens CoF is highlighted by studies that suggest that its increase may be associated with increased contact lens discomfort and corneal staining. 13,57,58 It has also been found that LWE can develop shortly after individuals start wearing contact lenses. 43 It is therefore conceivable that a regular and smooth surface (either contact lens or cornea) that comes in contact with the lid wiper is a prerequisite for a healthy lid wiper.…”
Section: 13mentioning
confidence: 99%